The Effect of Applying Role Play Technique on Students’ Speaking Ability at Grade Ten of SMA Swasta HKBP Nommensen Pematangsiantar - Daniel Alexander Panawari sipayung; Sahlan Tampubolon; Harpen Silitonga (Journal of Innovative and Creativity, 2025)
This study deals with the effect of applying the Role Play Technique on students’ speaking ability at grade ten of SMA Swasta HKBP Nommensen Pematangsiantar. The purpose of this research is to determine how the Role Play technique affects the students' speaking ability in grade tenth at SMA Kampus HKBP Nommensen Pematangsiantar with a total sample of 46 people. This research was implemented using a quantitative design, using an experimental approach as a research method. To determine how the Role Play technique affects the students’ speaking ability in grade tenth at SMA Swasta HKBP Nommensen Pematangsiantar, the T-test formula was used. From the test result, it is determined that the t-observed value is 4,23 and the t-table value is 2,015. If the t-observed > t-table, the alternative hypothesis, Ha, is acceptable. The score was calculated using a t-test with a degree of freedom of 44 (df=Nx+Ny-2), a level of significance of 0,05. The t-test calculation result indicated that the t-observed is greater than the t-table [t-obs (4,23) > t-table (2,015) {α=0,05} with df=44]., then the alternative hypothesis (Hs) is accepted. Therefore, this research showed that the Role Play technique affects the students’ speaking ability at grade tenth of SMA Kampus HKBP Nommensen Pematangsiantar.